Post-translational modifications of hnRNP A1 differentially modulate retroviral IRES-mediated translation initiation. Issue 18 (22nd September 2020) - Barrera, Aldo; Ramos, Hade; Vera-Otarola, Jorge; Fernández-García, Leandro; Angulo, Jenniffer; Olguín, Valeria; Pino, Karla; Mouland, Andrew J; López-Lastra, Marcelo
Abstract: The full-length mRNAs of the human immunodeficiency virus type-1 (HIV-1), the human T-cell lymphotropic virus type-1 (HTLV-1), and the mouse mammary tumor virus (MMTV) harbor IRESs. The activity of the retroviral-IRESs requires IRES-transacting factors (ITAFs), being hnRNP A1, a known ITAF for the HIV-1 IRES. In this study, we show that hnRNP A1 is also an ITAF for the HTLV-1 and MMTV IRESs. The MMTV IRES proved to be more responsive to hnRNP A1 than either the HTLV-1 or the HIV-1 IRESs. The impact of post-translational modifications of hnRNP A1 on HIV-1, HTLV-1 and MMTV IRES activity was also assessed. Results show that the HIV-1 and HTLV-1 IRESs were equally responsive to hnRNP A1 and its phosphorylation mutants S4A/S6A, S4D/S6D and S199A/D. However, the S4D/S6D mutant stimulated the activity from the MMTV-IRES to levels significantly higher than the wild type hnRNP A1. PRMT5-induced symmetrical di-methylation of arginine residues of hnRNP A1 enabled the ITAF to stimulate the HIV-1 and HTLV-1 IRESs while reducing the stimulatory ability of the ITAF over the MMTV IRES. We conclude that retroviral IRES activity is not only dependent on the recruited ITAFs but also relies on how these proteins are modified at the post-translational level.